Validity and reliability study of Pieper Pressure Ulcer test in Tuskish Nurses - GÜL, ASİYE (My University, 2019)
Aim: The aim of the cross-sectional and descriptive study was to determine validity and reliability Pieper Pressure Ulcer Knowledge Test (PUKT) in Turkish Nurses. Methods: The sample consists of Turkish nurses who working in a training and research hospital in the European side of Istanbul. Data were collected using the PUKT. The PUKT was developed by Pieper in 1993 to evaluate pressure ulcer prevention, staging of pressure ulcers, and wound identification of nurses' knowledge. Lawrence et al. validated modified Pieper Pressure Ulcer Information Test in 2015. The test consists of 49 items, a correct answer was scored 1, and an incorrect response was scored 0, thus, the possible score range was from 0 to 49. Results: The language validity and cultural adaptation were performed of the PUKT. In the analysis, which was conducted according to expert opinions, the content validity index (CVI=0.918) were determined. The reliability of the scale was examined with time invariance and internal consistency. In the test-retest test, there was no statistically significant difference between the two measurement results (t = -1.875, p = 0.06), the correlation coefficient was 0.840 and the relationship between them was statistically significant. The Kuder Richardson 20 value, which was calculated for testing internal reliability, was found to be 0.735. The Kappa value was determined to be 0.646; thus, the test had good interrater reliability. Conclusion: it has been determined that Turkish form of PUKT is appropriate measurement tool in terms of language and content validity to Turkish nursing.
Keywords: Nurses; Pressure Ulcer; Reliability; Validity; Hemşireler; Basınç Ülseri; Güvenilirlik; Geçerlik